Determining the level of motivation and attitude of students for classes in physical education in higher education institutions - T.V. Pavlenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Pressing questions of the motivation of students to attend physical education classes in high schools. Shows the level of their physical fitness. Presented by the personal attitude to studies and evaluated for a target orientation, forms and practical training. The study involved 79 students. It was stated that the motivation of students to the motor activity generated from them is wrong. Found that the greatest preference is given to students of the development of force: a meager 26 students (33%), flexibility 20 students (25.3%), speed 18 students (22.8%), endurance 11 students (13.9 %), agility 4 students (5%). The data on the poor state of physical fitness of today's youth and its negative attitude to physical education and sport.